Identifikasi Etnokimia dari Makanan Tradisional Sepat Dari Masyarakat Sumbawa di Nusa Tenggara Barat - Andayani, Yayuk; Riza, Yunisa; Hakim, Aliefman (FKIP University of Mataram, 2025)
This study aims to identify the chemical knowledge (ethno-chemistry) of traditional food of the Sumbawa community, namely sepat. The research is qualitative with a phenomenological approach, using key informants as sources of information. The key informants are customary leaders or members of the Sumbawa community who have in-depth knowledge about the traditional food sepat. Information was obtained through observation and interviews using validated instruments. The data were analyzed descriptively using the Miles–Huberman method, which includes the stages of data collection, data reduction, presentation, data verification, and conclusion. The identification results found that in traditional sepat food, there is a connection with chemistry concepts, including: food chemistry, proteins, chemical reactions, acids and bases, energetics, systems and environment, solutions and mixtures. It is hoped that these findings can help teachers, students, and education observers in developing teaching materials or learning resources based on local culture.